Exploring Mobility Solutions: Design and Performance Analysis of a Two-Wheel Rover System (International Journal of Communication Systems and Network Technologies, 2021)
This paper introduces a Two-Wheel Rover system designed for enhanced mobility in constrained environments. Focused on achieving optimal balance, maneuverability, and energy efficiency, the system integrates advanced control algorithms, cutting-edge sensors, and a robust mechanical structure. The study provides a detailed overview of the system's architecture, encompassing mechanical and electrical design, sensor integration, control strategies, and power management. Performance analysis includes rigorous assessments of motion control algorithms, navigation precision, obstacle avoidance, stability, maneuvering capabilities, and energy utilization. The experimental setup details hardware components, software tools, and testing environments used for evaluation. Results highlight the system's effectiveness in real-world scenarios, with comparative insights against existing solutions. The paper concludes by addressing encountered challenges, outlining limitations, and proposing avenues for future enhancements, positioning the Two-Wheel Rover as a promising solution for agile and adaptable robotic applications.
Keywords: Two-Wheel Rover; Mobility Solutions; Robotic Systems; Control Algorithms; Sensor Integration; Mechanical Design; Energy Efficiency; Agile Robotics; Maneuverability; Autonomous Navigation